Helliconia spring - Aldiss, Brian Wilson, 1925-
This novel unfolds the story of Helliconia, a planet caught in an epic cycle of seasonal change. As it shifts from centuries of winter into a vibrant spring, human civilizations begin to emerge and fight against the powerful phagors. The narrative explores the characters’ struggles within this grand cosmic setting. [By Publisher]